What affects second language vocabulary learning? Evidence from multivariate analysis - Sun, Danning; Chen, Zihan; Zhu, Shanhua (Frontiers in Education, 2023)
Vocabulary acquisition plays a pivotal role in second language (L2) learning, prompting extensive research into learner variables and vocabulary strategies. This study offers a comprehensive examination of the intricate factors influencing vocabulary knowledge among 200 Chinese learners who learn English as a foreign language (EFL), emphasizing the necessity of a multifaceted approach to enhance vocabulary acquisition. Our investigation unveils that L2 proficiency stands as the most robust predictor of vocabulary knowledge, closely trailed by vocabulary learning strategies, age of acquisition (AoA), and classroom exposure. Notably, the age at which Chinese EFL learners are initially exposed to their L2 significantly impacts vocabulary knowledge, with earlier exposure yielding more substantial vocabulary knowledge. Contrary to conventional beliefs, our study challenges the notion that extended classroom sessions lead to superior vocabulary knowledge. This highlights the critical need to reassess pedagogical practices in language instruction and optimize classroom time efficiency. Furthermore, we emphasize the pivotal role of vocabulary learning strategies, indicating that learners with broader vocabulary knowledge tend to exhibit greater selfregulation, initiative, and self-awareness in vocabulary acquisition. Pedagogical implications for vocabulary researchers and instructors were provided.